Production of Human Erythropoietin in Transgenic Canola Employing the Technology of Oleosin Fusion - Corin Newman (The Journal of Undergraduate Research, 2013)
Human erythropoietin (EPO) is an endogenous cytokine that is responsible for the stimulation of the production of erythrocytes. Purified EPO is mainly used for treatment of anemia. Many conditions can result in unhealthy anemic levels; therefore, EPO can be used to care for many differing ailments. EPO was first successfully cloned in 1984. Since then, it has been produced in yeast, bacteria and insect cells. Additionally, it has been synthesized transgenically in plants. Mammalian cell systems have been shown to possess the highest efficiency for producing EPO, even though they require high cost; however, the appeal of using plant environments to transgenically produce proteins is extremely alluring due to its cost efficiency. One plant that has been shown valuable in its ability to transgenically accumulate proteins is Brassica napus, commonly known as canola. Canola has shown the capability of transgenically producing the hirudin protein through oleosin-fusion technology. This technology has been suggested to produce extremely stable recombinant proteins that exhibit their normally expected activity. Thus, here is proposed the employment of oleosin-fusion techniques as template to produce recombinant EPO (rhEPO) in canola. If successful, this project will exhibit a new, stable and cost efficient method of producing the rhEPO that is so highly desired within the biopharmaceutical market.